Positive electrode active material, method of preparing same, positive electrode including same, and rechargeable lithium battery including positive electrode
By forming a double-coated structure of aluminum and nickel on the surface of layered lithium nickel-manganese composite oxide core particles, the problem of cobalt shortage and accelerated side reactions under high temperature and high pressure conditions is solved, and an efficient and economical positive electrode active substance is achieved, which improves the capacity and cycle life of lithium batteries.
Patent Information
- Application Number
- CN202411174547.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-24
- Filing Date
- 2024-08-26
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, there is a shortage of supply of positive electrode active substances including rare metal cobalt, and under high voltage and high temperature conditions, the side reaction between the positive electrode active substances and the electrolyte is accelerated, resulting in an increase in the amount of gas generation and deterioration of the cycle life characteristics.
A positive electrode active material including layered lithium nickel-manganese composite oxides is used, which forms a first coating of aluminum and a second coating of nickel on the surface of the nuclear particles, thereby maximizing capacity and efficiency through this structure while suppressing side reactions at high voltage and high temperatures.
It achieves economic benefits, appropriately high capacity and long cycle life characteristics, and reduces gas generation under high voltage and high temperature conditions, improving the overall performance of the battery.
Smart Images

Figure CN119542371A_ABST
Abstract
Description
Technical Field
[0001] One or more aspects of embodiments of the present disclosure are directed to a positive electrode active material, a method for preparing the same, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode. Background Art
[0002] Portable information devices (such as cellular phones, laptop computers, smart phones, etc.) and / or electric vehicles may use rechargeable lithium batteries with relatively high energy density and easy or appropriate portability as driving power sources. Recently, active research has been conducted on the application of rechargeable lithium batteries with high energy density as driving power sources for hybrid and / or electric vehicles and / or power storage power sources for home power storage units and / or power walls.
[0003] Efforts have been made to study various positive electrode active materials to obtain rechargeable lithium batteries suitable for the above-mentioned applications. Among them, lithium nickel oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides and / or lithium cobalt oxides can be used as positive electrode active materials. However, although the demand for rechargeable lithium batteries with relatively large size, high capacity and / or high energy density has increased recently, the supply of positive electrode active materials including rare metal cobalt is expected to be in short supply or seriously insufficient. In fact, because cobalt is expensive and the remaining reserves are small, it is necessary or desirable to develop positive electrode active materials that do not include (e.g., exclude) cobalt and / or include cobalt in a reduced content (e.g., amount). Summary of the invention
[0004] One or more aspects of embodiments of the present disclosure relate to a positive electrode active material including a layered lithium nickel manganese composite oxide, a method for preparing the same, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode, the positive electrode active material ensuring (e.g., achieving) economic benefits, appropriately high capacity and appropriately long cycle life characteristics, and having improved high voltage and high temperature characteristics. Additional aspects will be stated in part in the subsequent description, and in part will be apparent from the description, or can be understood by practicing the presented embodiments of the present disclosure.
[0005] One or more embodiments provide a positive electrode active material including: a core particle including a layered lithium nickel manganese-based composite oxide, a first coating layer provided on a surface of the core particle and including aluminum (Al), and a second coating layer provided on the first coating layer and including nickel (Ni).
[0006] One or more embodiments provide a method for preparing the positive electrode active material of the present embodiment, which includes: mixing a layered nickel manganese composite hydroxide and a lithium raw material, and performing a first heat treatment to obtain a lithium nickel manganese composite oxide; adding an Al raw material to an aqueous solvent, adding a lithium nickel manganese composite oxide thereto and mixing them, and then adding a Ni raw material and mixing them; and drying the mixture and performing a second heat treatment.
[0007] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes the positive electrode active material of the present embodiment.
[0008] One or more embodiments provide a rechargeable lithium battery including: the positive electrode of the present embodiment, a negative electrode, and an electrolyte.
[0009] According to the positive electrode active material of the present embodiment, its capacity can be maximized or increased while minimizing or reducing production costs, can ensure or achieve appropriately long cycle life characteristics, and can improve high voltage and high temperature characteristics. Accordingly, the rechargeable lithium battery using the positive electrode active material can exhibit appropriately high initial charge / discharge capacity and efficiency even under high voltage driving conditions, can achieve appropriately long cycle life characteristics, and can effectively or appropriately suppress or reduce the gas generation problem caused by high voltage and high temperature driving. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] These and / or other aspects will become apparent and more easily understood through the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0011] Figure 1 to Figure 4 Each is a cross-sectional view schematically showing a rechargeable lithium battery according to one or more embodiments.
[0012] Figure 5 This is a HR-STEM (High Resolution Scanning Transmission Electron Microscope) image of a cross section of the positive electrode active material of Example 1.
[0013] Figure 6 This is an EDS (Energy Dispersive X-ray Spectroscopy) analysis image, which highlights Ni in the cross section of the positive electrode active material of Example 1.
[0014] Figure 7 This is an EDS analysis image, which highlights Al in the cross section of the positive electrode active material of Example 1.
[0015] Reference numerals
[0016] 100: Rechargeable lithium battery 10: Positive electrode
[0017] 11: Positive electrode lead lug 12: Positive electrode terminal
[0018] 20: Negative electrode 21: Negative electrode lead lug
[0019] 22: Negative electrode terminal 30: Separator
[0020] 40: Electrode assembly 50: Housing
[0021] 60: Sealing member 70: Electrode terminal piece
[0022] 71: Positive electrode terminal tab 72: Negative electrode terminal tab DETAILED DESCRIPTION
[0023] Hereinafter, specific embodiments will be described in more detail so that those skilled in the art can easily implement them. However, the present disclosure may be implemented in many different forms and is not to be construed as limited to the example embodiments set forth herein.
[0024] The terms used herein are only used to describe the embodiments and are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.
[0025] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like, of the components.
[0026] Herein, it should be understood that terms such as “comprises,” “includes,” or “have” are intended to indicate the presence of the implemented features, quantities, steps, elements, or combinations thereof, but it does not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.
[0027] In the drawings, the size (e.g., thickness) of layers, films, panels, regions, etc., is exaggerated for clarity, and the same reference numerals represent the same elements throughout the specification. It will be understood that when an element (such as a layer, film, region, or substrate) is referred to as being "on" another element (such as a layer, film, region, or substrate), it can be directly on the other element (such as a layer, film, region, or substrate), or there may also be intervening elements. In contrast, if an element is referred to as being "directly on" another element (such as a layer, film, region, or substrate), there are no intervening elements.
[0028] As used herein, the term "layer" includes not only shapes formed on the entire (e.g., the entire or substantially the entire) surface, but also shapes formed on a partial surface when viewed in a plan view. Herein, the phrase "on a plane" or "in a plan view" means observing the target portion from the top, and the phrase "in a cross section" means observing a cross section formed by vertically cutting the target portion from the side. Unless otherwise specified, the average particle size (D 50 ) may refer to the diameter of particles having a cumulative volume of 50% by volume in a particle size distribution. As used herein, when no other definition is provided, the average particle size (D 50 ) means the diameter of particles with a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size of about 20 particles in a scanning electron microscope image (for spherical particles, the diameter; or for non-spherical particles, the length of the major axis). In addition, the average particle diameter can be measured by any appropriate method available to those skilled in the art, for example, it can be measured by a particle size analyzer, and / or it can be measured by a transmission electron microscope image and / or a scanning electron microscope image. Alternatively, the average particle diameter value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles for each particle size range, and calculating therefrom.
[0029] In this document, "or" is not interpreted as an exclusive meaning. For example, "A or B" is interpreted to include A, B, A+B, etc.
[0030] As used herein, expressions such as “at least one of,” “one of,” and “selected from,” when preceding / following a list of elements, modify the entire list of elements and do not modify the individual elements of the list. For example, “at least one selected from a, b, and c,” “at least one of a, b, and c,” etc. may indicate only a, only b, only c, both a and b (e.g., simultaneously), both a and c (e.g., simultaneously), both b and c (e.g., simultaneously), all of a, b, and c, or variations thereof.
[0031] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0032] Further, when describing embodiments of the present disclosure, the use of “may” refers to “one or more embodiments of the present disclosure.”
[0033] It will be understood that although the terms first, second, etc. may be used to describe various elements in this article, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element. Therefore, without departing from the teachings of the present invention, the first element may be referred to as the second element. Similarly, the second element may be referred to as the first element.
[0034] As used herein, the terms "use," "using," and "used" may be considered synonymous with the terms "utilize," "utilizing," and "utilized," respectively.
[0035] For ease of describing the relationship of one element or feature to another element or feature as illustrated in the figures, spatially relative terms such as "under," "below," "below," "above," "up," "bottom," "top," etc. may be used herein. It will be understood that the spatially relative terms are intended to encompass different orientations of the device in use or operation in addition to the orientation depicted in the drawings. For example, when the device in the drawings is turned over, an element described as being "under" or "below" other elements or features will then be oriented "above" or "on" the other elements or features. Thus, the term "under" may encompass both orientations above and below. The device may be oriented in other ways (rotated 90 degrees or in other orientations), and the spatially relative descriptors used herein should be interpreted accordingly.
[0036] As used herein, the terms "substantially," "about," and similar terms are used as terms of approximation rather than as terms of degree, and are intended to account for the inherent deviations in measured or calculated values that would be recognized by one of ordinary skill in the art. "About" or "approximately" as used herein include the stated value and mean within an acceptable range of deviation for the particular value determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" may mean within one or more standard deviations of the stated value, or within ±30%, ±20%, ±10%, or ±5% of the stated value.
[0037] Any numerical range set forth in this article is intended to include all sub-ranges of the same numerical precision falling within the set forth range. For example, the range of "1.0-10.0" is intended to be included between the set forth minimum value 1.0 and the set forth maximum value 10.0 (including 1.0 and 10.0), that is, all sub-ranges (such as, for example, 2.4-7.6) having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0. Any maximum numerical limit set forth in this article is intended to include all lower numerical limits falling therein, and any minimum numerical limit set forth in this specification is intended to include all higher numerical limits falling therein. Accordingly, the applicant reserves the right to modify this specification (including claims) to explicitly set forth any sub-range falling within the range explicitly set forth in this article.
[0038] The term "metal" is to be interpreted as a concept including common metals, transition metals and / or metalloids (semimetals).
[0039] Positive electrode active material
[0040] Some embodiments provide a positive electrode active material, which includes: a core particle including a layered lithium nickel manganese composite oxide (hereinafter, may be simply referred to as "lithium nickel manganese composite oxide"), a first coating layer provided on the surface of the core particle and including Al, and a second coating layer provided on the first coating layer and including Ni.
[0041] Recently, as the price of rare metal cobalt has soared sharply (e.g., has increased significantly), there is an increased demand or expectation for the development of positive electrode active materials that exclude (do not include) cobalt (e.g., cobalt-free) or include cobalt in a reduced amount. Among them, positive electrode active materials having an olivine crystal structure (such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP) and / or lithium manganese iron phosphate (LMFP)) and / or positive electrode active materials having a spinel crystal structure (such as lithium manganese oxide (LMO)) are limited in achieving high capacity due to the relatively small available lithium capacity in their structure. Lithium nickel manganese positive electrode active materials having a layered structure can exhibit excellent or improved capacity and efficiency characteristics due to the relatively large amount of available lithium in their structure, and are therefore suitable for high-capacity batteries, but as cobalt, which plays an important (even critical) role in the layered structure, is excluded, structural stability may deteriorate, resistance may increase, and thus lithium nickel manganese positive electrode active materials may not be able to ensure appropriate long-term cycle life characteristics. In addition, due to the exclusion (non-inclusion) of cobalt, undesirable side reactions of the positive electrode active material with the electrolyte may be accelerated under high voltage and high temperature conditions, causing problems of increased gas generation and deterioration of cycle life characteristics.
[0042] According to some embodiments, by introducing a first coating layer and a second coating layer on the surface of the layered lithium nickel manganese based composite oxide core particles, the capacity and efficiency are maximized or increased, and the amount of gas generation is reduced even under high voltage and / or high temperature conditions, thereby providing a positive electrode active material having appropriately long cycle life characteristics.
[0043] Nuclear particles
[0044] The core particles include lithium nickel manganese composite oxides. Based on 100mol% of the total metals other than lithium in the lithium nickel manganese composite oxide, the nickel content (e.g., amount) in the lithium nickel manganese composite oxide may be greater than or equal to about 60mol%, for example, about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol% or about 60mol% to about 75mol%. If (e.g., when) the nickel content (e.g., amount) meets any one of the above ranges (when), even if the cobalt content (e.g., amount) is reduced, a suitably high capacity can be achieved, and structural stability can be increased.
[0045] Based on 100 mol% of the total metal other than lithium in the lithium nickel manganese composite oxide, the manganese content (e.g., amount) may be, for example, greater than or equal to about 10 mol%, for example, about 10 mol% to about 40 mol%, about 15 mol% to about 35 mol%, about 15 mol% to about 30 mol%, or about 20 mol% to about 30 mol%. If (e.g., when) the manganese content (e.g., amount) satisfies any one of the above ranges, the positive electrode active material can improve structural stability while achieving a suitably high capacity.
[0046] For example, the lithium nickel manganese composite oxide may be, for example, a lithium nickel manganese aluminum composite oxide further including aluminum in addition to nickel and manganese. If (for example, when) the lithium nickel manganese composite oxide includes aluminum (when), even if the cobalt element is excluded from the structure (the cobalt element is not included in the structure), it is also beneficial to maintain a suitable stable layered structure. The aluminum content (for example, amount) of the lithium nickel manganese composite oxide based on 100mol% may be greater than 0mol% and less than or equal to 3mol%, for example, greater than or equal to about 0.1mol%, greater than or equal to about 0.5mol% or greater than or equal to about 1mol%, for example, about 1mol% to about 3mol%, about 1mol% to about 2.5mol%, about 1mol% to about 2mol% or about 1.5mol% to about 2.5mol%. If the aluminum content (for example, amount) satisfies any one of the above ranges, even if cobalt is excluded, a suitable stable layered structure can be maintained, the problem of structural collapse caused by charging and discharging can be suppressed or reduced, and the appropriately long cycle life characteristics of the positive electrode active material can be achieved.
[0047] According to some embodiments, the concentration of aluminum in the core particle can be uniform or substantially uniform. For example, it means or refers to the absence of a concentration gradient of aluminum from the center to the surface in the core particle, or the aluminum concentration in the outer part of the core particle is neither significantly higher than nor significantly lower than the aluminum concentration in the inner part of the core particle, and the aluminum is uniformly or substantially uniformly distributed in the core particle. According to the present embodiment, this structure can be obtained by synthesizing a lithium nickel manganese aluminum composite oxide as follows: using a nickel manganese aluminum composite hydroxide as a precursor, using an aluminum raw material (hereinafter, also referred to as "Al raw material") during the preparation of the precursor, and not additionally doping aluminum during the synthesis of the core particle. The core particle may be in the form of a secondary particle in which a plurality of primary particles are aggregated, and the aluminum content (e.g., amount) inside the primary particle may be the same or similar, regardless of the position of the primary particle in the secondary particle. For example, if (for example, when) a primary particle is selected at any position in the cross section of a secondary particle to measure the aluminum content (for example, amount) not at the interface of the primary particle but inside the primary particle, the aluminum content (for example, amount) can be the same / similar / substantially uniform regardless of the position of the primary particle (i.e., whether the primary particle is near the center of the secondary particle or near its surface). In this structure, even if cobalt is not present, or is present in a very small amount (for example, less than or equal to 0.1 mol% based on 100 mol% of all metals other than lithium in the layered lithium nickel manganese composite oxide), the layered structure can be appropriately stably maintained, and aluminum byproducts and / or aluminum aggregates are not generated (or substantially not generated), thereby simultaneously (or synchronously) improving the capacity, efficiency and cycle life characteristics of the positive electrode active material.
[0048] The lithium nickel manganese-based composite oxide may be represented by Chemical Formula 1.
[0049] Chemical formula 1
[0050] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 .
[0051] In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 It may be one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X may be one or more elements selected from F, P and S.
[0052] In Chemical Formula 1, 0.9 ≤ a1 ≤ 1.5, or 0.9 ≤ a1 ≤ 1.2. If Chemical Formula 1 includes aluminum, it may satisfy 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 ≤ z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29. For example, 0.6 ≤ x1 ≤ 0.8, 0.1 ≤ y1 ≤ 0.39, 0.01 < z1 ≤ 0.03, and 0 ≤ w1 ≤ 0.29.
[0053] In Chemical Formula 1, for example, 0.6 ≤ x1 ≤ 0.79, 0.6 ≤ x1 ≤ 0.78, 0.6 ≤ x1 ≤ 0.75, 0.65 ≤ x1 ≤ 0.8, or 0.7 ≤ x1 ≤ 0.79; 0.1 ≤ y1 ≤ 0.35, 0.1 ≤ y1 ≤ 0.30, 0.1 ≤ y1 ≤ 0.29, 0.15 ≤ y1 ≤ 0.39, or 0.2 ≤ y1 ≤ 0.3; 0.01 ≤ z1 ≤ 0.025, 0.01 < z1 ≤ 0.02, or 0.01 < z1 ≤ 0.019; and 0 ≤ w1 ≤ 0.28, 0 ≤ w1 ≤ 0.27, 0 ≤ w1 ≤ 0.26, 0 ≤ w1 ≤ 0.25, 0 ≤ w1 ≤ 0.24, 0 ≤ w1 ≤ 0.23, 0 ≤ w1 ≤ 0.22, 0 ≤ w1 ≤ 0.21, 0 ≤ w1 ≤ 0.2, 0 ≤ w1 ≤ 0.15, 0 ≤ w1 ≤ 0.1, or 0 ≤ w1 ≤ 0.09.
[0054] The lithium nickel manganese composite oxide may be a cobalt-free compound that does not include cobalt or includes very little or substantially little cobalt. For example, based on all metals other than lithium in 100 mol% of the lithium nickel manganese composite oxide, the lithium nickel manganese composite oxide may have a cobalt content (e.g., amount) of at most 0.01 mol% (e.g., about (e.g., greater than) 0 mol% to about 0.01 mol%).
[0055] The core particles may be in the form of secondary particles made by aggregating a plurality of primary particles. The secondary particles may be spherical, elliptical, polyhedral, and / or irregular in shape, and the primary particles may be spherical, elliptical, plate-shaped, or a combination thereof.
[0056] If (e.g., when) the battery operates under high voltage and / or high temperature conditions, the core particles are vulnerable to chemical attack by components in the electrolyte, and an undesired side reaction with the electrolyte may occur. As a result, the amount of gas generated may be inappropriately or undesirably high, which reduces the cycle life and safety of the battery. These problems can be solved by introducing a coating according to the present embodiment, which will be discussed in more detail below.
[0057] The first coating
[0058] Based on 100 mol% of all metals other than lithium in the positive electrode active material, the Al content (e.g., amount) in the first coating layer may be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%. These ranges correspond only to the content (e.g., amount) of aluminum contained in the first coating layer, and are separated from the aluminum contained in the core particles (e.g., excluding the aluminum contained in the core particles). The aluminum content in the first coating layer can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. If the aluminum content in the first coating layer satisfies any one of the above ranges, a uniform (or substantially uniform) and appropriately thin coating layer can be formed, the resistance of the positive electrode active material will not increase (or substantially not increase), and the side reaction with the electrolyte can be effectively or appropriately suppressed or reduced, so that the cycle life characteristics of the rechargeable lithium battery can be improved under high voltage and / or high temperature conditions. For example, if the aluminum content of the first coating layer is too much, a uniform (or substantially uniform) coating layer may not be formed and / or the resistance may increase undesirably, which may reduce the charge and discharge efficiency and cycle life characteristics, and if the aluminum content of the first coating layer is too little, a coating layer of suitable or appropriate thickness may not be formed, which may reduce the effect of suppressing or appropriately reducing side reactions with the electrolyte.
[0059] The first coating may be in the form of a film that continuously covers the surface of the core particle, for example, it may be in the form of a shell covering the entire (or substantially the entire) surface of the core particle. This is different from a structure in which the coating is applied to a portion of the surface of the core particle (for example, in contrast to a structure in which the coating is applied to a portion of the surface of the core particle). According to some embodiments, because the first coating is formed to completely cover the surface of the core particle, but still has a very or appropriately thin and uniform (or substantially uniform) thickness, the positive electrode active material may not show an increase in resistance (for example, an undesirable increase) or capacity degradation (for example, undesirable degradation), but may improve structural stability, effectively or appropriately suppress side reactions with the electrolyte, reduce the amount of gas generation, and achieve a suitable long-term cycle life characteristic.
[0060] The thickness of the first coating layer may be about 5 nanometers (nm) to about 40 nm, for example, about 5 nm to about 30 nm or about 5 nm to about 20 nm. If (for example, when) the thickness of the first coating layer satisfies any one of the above ranges, the structural stability of the positive electrode active material can be improved without increasing the resistance or reducing the capacity due to the coating layer, and the side reaction with the electrolyte can be effectively or appropriately suppressed or reduced. The thickness of the coating layer can be measured by, for example, SEM (scanning electron microscopy), TEM (transmission electron microscopy), TOF-SIMS (time of flight-secondary ion mass spectrometry), XPS (X-ray photoelectron spectroscopy) and / or EDS (energy dispersive X-ray spectroscopy) analysis, for example, by TEM-EDS line profile.
[0061] The first coating may be thicker than the second coating, as will be described in more detail below.
[0062] The first coating of the positive electrode active material has a thickness of several nanometers to tens of nanometers, and therefore has a suitably thin and substantially uniform thickness. For example, within a positive electrode active material particle, the first coating has a thickness deviation of less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the thickness deviation of the coating refers to the deviation of the thickness of the coating within a positive electrode active material particle. The thickness deviation of the coating can be obtained, for example, by measuring the thickness at each of approximately 10 points in an electron microscope image of a cross-section of a positive electrode active material particle, calculating its arithmetic mean, and then dividing the absolute value of the difference between one measurement data and the arithmetic mean by the arithmetic mean and multiplying by 100. If (for example, when) the thickness deviation and / or standard deviation of the first coating satisfies any one of these ranges, the first coating can be well or appropriately formed as a film having a uniform (or substantially uniform) thickness on the surface of the core particles of the positive electrode active material, and thereby improve the structural stability of the positive electrode active material, and effectively or appropriately inhibit or reduce side reactions with the electrolyte, and minimize or reduce the increase in resistance and / or capacity degradation due to the coating.
[0063] The first coating layer may include, for example, aluminum oxide, lithium aluminum oxide, or a combination thereof. The first coating layer may have a layered structure. For example, the compound included in the first coating layer may have a layered structure.
[0064] In addition to aluminum, the first coating may further include nickel, manganese, or a combination thereof.
[0065] Second coating
[0066] Based on 100 mol% of all metals other than lithium in the positive electrode active material, the Ni content (e.g., amount) in the second coating layer may be about 0.01 mol% to about 1 mol%, such as about 0.01 mol% to about 0.9 mol%, about 0.01 mol% to about 0.7 mol%, about 0.05 mol% to about 0.5 mol%, or about 0.1 mol% to about 0.4 mol%. The Ni content in the second coating layer may be measured, for example, by SEM-EDS analysis of the surface and / or cross section of the positive electrode active material. If the Ni content in the second coating layer satisfies any one of the above ranges, a uniform (or substantially uniform) and appropriately thin coating layer may be formed, the resistance of the positive electrode active material may not increase (or undesirably increase), and side reactions (e.g., undesirable side reactions) with the electrolyte may be effectively or appropriately suppressed or reduced, so that the cycle life characteristics of the rechargeable lithium battery may be improved under high voltage and / or high temperature conditions. For example, if the Ni content of the second coating layer is too much, a uniform (or substantially uniform) coating layer may not be formed and / or the resistance may increase, which may reduce the charge and discharge efficiency and cycle life characteristics, and if the Ni content of the second coating layer is too little, a coating layer of suitable or appropriate thickness may not be formed, the effect of inhibiting or reducing side reactions with the electrolyte may be reduced, and / or the charge efficiency / discharge efficiency and / or high temperature cycle life characteristics may be reduced.
[0067] The second coating layer may be in the form of a film and / or shell that continuously surrounds the surface of the first coating layer. According to some embodiments, because the second coating layer is formed to completely cover the outermost surface of the positive electrode active material, but still has a very or appropriately thin and uniform (or substantially uniform) thickness, the positive electrode active material may not show an increase in resistance (e.g., an undesirable increase) or deterioration in capacity, but may improve structural stability, effectively or appropriately inhibit or reduce side reactions with the electrolyte, reduce gas generation, and / or achieve long-term cycle life characteristics.
[0068] The thickness of the second coating layer may be less than or equal to about 10 nm, for example, about 0.1 nm to about 10 nm, about 0.5 nm to about 9 nm, about 1 nm to about 7 nm, or about 1 nm to about 5 nm. If (for example, when) the thickness of the second coating layer satisfies any one of the above ranges, the structural stability of the positive electrode active material can be improved without increasing (or undesirably increasing) resistance or reducing (or undesirably reducing) capacity due to the coating layer, and the side reaction with the electrolyte can be effectively or appropriately suppressed or reduced. The thickness of the coating layer can be measured by, for example, SEM, TEM, TOF-SIMS, XPS and / or EDS analysis, for example, by TEM-EDS line profile.
[0069] The second coating layer may be thin, at the level of several nanometers, and may have a uniform (or substantially uniform) thickness. For example, within a positive electrode active material particle, the second coating layer has a thickness deviation of less than or equal to about 20%, less than or equal to about 18%, or less than or equal to about 15%. In this article, the thickness deviation of the coating layer refers to the deviation of the thickness of the coating layer within a positive electrode active material particle. The thickness deviation of the coating layer can be obtained, for example, by measuring the thickness at each of about 10 points in an electron microscope image of a cross-section of a positive electrode active material particle, calculating its arithmetic mean, and then dividing the absolute value of the difference between one measurement data and the arithmetic mean by the arithmetic mean and multiplying by 100. If (for example, when) the thickness deviation and / or standard deviation of the second coating satisfies any one of the above ranges, the second coating can be well or appropriately formed as a film with uniform (or substantially uniform) thickness on the outermost surface of the core particle of the positive electrode active material, and thereby improve the structural stability of the positive electrode active material, and effectively or appropriately inhibit or reduce side reactions with the electrolyte, and minimize or reduce the resistance increase and / or capacity degradation due to the coating.
[0070] In addition to Ni, the second coating may further include Al. The second coating may include, for example, nickel oxide, lithium nickel oxide, aluminum nickel oxide, lithium aluminum nickel oxide, or a combination thereof. The second coating may have a layered structure. Because the core, the first coating, and the second coating all have a layered crystal structure, the insertion and extraction of lithium can be further promoted.
[0071] In some embodiments, the first coating layer may be thicker than the second coating layer. For example, the ratio of the thickness of the second coating layer to the thickness of the first coating layer may be less than about 0.5, for example, less than or equal to about 0.4 or less than or equal to about 0.3. If the thickness of the first coating layer and the thickness of the second coating layer satisfy this relationship, the structural stability of the positive electrode active material can be improved without increasing (e.g., undesirably increasing) resistance or reducing (e.g., undesirably reducing) capacity due to the coating layer, and the positive electrode active material can effectively or appropriately suppress or reduce side reactions with the electrolyte to improve high voltage characteristics and / or high temperature characteristics.
[0072] The Al content (e.g., amount) of the first coating layer may be greater than the Ni content of the second coating layer. In this article, the content may refer to the molar content and may refer to the molar content of metals other than lithium relative to 100 mol% in the positive electrode active material. For example, the ratio of the Ni content of the second coating layer to the Al content of the first coating layer may be less than about 0.5, for example, less than or equal to about 0.4 or less than or equal to about 0.3. If the Al content in the first coating layer and the Ni content in the second coating layer satisfy this relationship, the structural stability of the positive electrode active material can be improved without increasing (e.g., undesirably increasing) resistance or reducing (e.g., undesirably reducing) capacity due to the coating layer, and the side reaction with the electrolyte can be effectively or appropriately suppressed or reduced to improve high voltage characteristics and / or high temperature characteristics.
[0073] Grain boundary coating part
[0074] According to one or more embodiments, during the process of forming the first coating, aluminum may diffuse into the core particles. Accordingly, the positive electrode active material according to some embodiments may further include a grain boundary coating portion located on the surface of the primary particle inside the secondary particle and containing aluminum. In this article, the secondary particle refers to the core particle, and the interior of the secondary particle may refer to the entire internal portion except the surface of the secondary particle, for example, from the center of the secondary particle toward the surface of the secondary particle is at most about 60% of the length of the radius of the secondary particle (i.e., the distance from the surface of the secondary particle to the center of the secondary particle). The grain boundary coating portion is a different concept from the coating on the surface of the core particle, and refers to the coating portion on the surface of the primary particle inside the core particle. The presence of the grain boundary coating portion can be checked by using SEM-EDS analysis of a cross section of the positive electrode active material, etc. If (for example, when) an aluminum grain boundary coating portion is formed, the positive electrode active material can be further stabilized in structure and the cycle life characteristics can be improved.
[0075] The aluminum content (eg, amount) in the grain boundary coating portion is not particularly limited, but may be, for example, smaller than the aluminum content in the first coating layer.
[0076] In some embodiments, the grain boundary coating portion may further include nickel, manganese, yttrium, or a combination thereof in addition to aluminum.
[0077] The average particle size (D 50 ) is not particularly limited, but can be, for example, about 1 micron or micrometer (μm) to about 25 μm, about 5 μm to about 20 μm, about 10 μm to about 20 μm, about 11 μm to about 18 μm, or about 12 μm to about 15 μm. The average particle size (D 50) may refer to the diameter of particles (e.g., secondary particles) with a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image of the positive electrode active material. If (e.g., when) the average particle size of the positive electrode active material satisfies any one of the above ranges, a suitably high capacity and / or long cycle life may be achieved, and may be advantageous for forming a coating according to some embodiments.
[0078] In the positive electrode active material according to some embodiments, the cobalt content (e.g., amount) may be, for example, less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, less than or equal to about 0.001 mol%, or, for example, from about 0 mol% to about 0.01 mol%, based on 100 mol% of all metals other than lithium in the positive electrode active material. According to some embodiments, the positive electrode active material may be, for example, a cobalt-free positive electrode active material.
[0079] In one or more embodiments, the positive electrode active material according to some embodiments may not include (e.g., may exclude) sodium. Sodium ions may be used in the process of preparing the positive electrode active material, but according to the preparation method described in more detail below, core particles having a suitably stable structure and a coating having a uniform (or substantially uniform) thickness may be formed without using sodium ions.
[0080] Method for preparing positive electrode active material
[0081] In one or more embodiments, the method for preparing a positive electrode active material includes: mixing a layered nickel manganese composite hydroxide and a lithium raw material, and performing a first heat treatment to obtain a layered lithium nickel manganese composite oxide; adding an Al raw material to an aqueous solvent, adding a layered lithium nickel manganese composite oxide thereto and mixing them, and then adding a Ni raw material and mixing them; and drying the mixture and performing a second heat treatment. The positive electrode active material according to the present embodiment can be prepared by the above method.
[0082] The layered nickel-manganese composite hydroxide (i.e., nickel-manganese composite hydroxide) is a precursor of the core particles and may be in the form of secondary particles in which a plurality of primary particles are aggregated, and may not contain cobalt or may contain a very small amount of cobalt (e.g., less than or equal to 0.1 mol% based on 100 mol% of all metals in the nickel-manganese composite hydroxide). For example, it may be a cobalt-free nickel-manganese composite hydroxide. The nickel-manganese composite hydroxide may be prepared by an appropriate coprecipitation method.
[0083] Based on 100mol% of the total metal in the layered nickel-manganese composite hydroxide, the nickel content (e.g., amount) in the layered nickel-manganese composite hydroxide may be greater than or equal to about 60mol%, for example, about 60mol% to about 80mol%, about 65mol% to about 80mol%, about 70mol% to about 80mol%, about 60mol% to about 79mol%, about 60mol% to about 78mol%, or about 60mol% to about 75mol%. If (e.g., when) the nickel content (e.g., amount) satisfies the above range (when), even if the cobalt content (e.g., amount) is reduced, a suitably high capacity can be achieved, and structural stability can be increased.
[0084] The manganese content (e.g., amount) in the layered nickel-manganese-based composite hydroxide may be greater than or equal to about 10 mol%, for example, about 10 mol% to about 40 mol%, about 15 mol% to about 39 mol%, about 15 mol% to about 35 mol%, about 15 mol% to about 30 mol%, or about 20 mol% to about 30 mol%, based on 100 mol% of total metals in the layered nickel-manganese-based composite hydroxide.
[0085] In one or more embodiments, if (for example, when) the layered nickel-manganese composite hydroxide further includes aluminum (that is, the nickel-manganese composite hydroxide is a nickel-manganese-aluminum composite hydroxide), then based on 100 mol% of the total metal, the aluminum content (for example, amount) may be up to 3 mol%, greater than or equal to about 0.1 mol%, greater than or equal to about 0.5 mol%, or greater than or equal to about 1 mol%, for example, about 1 mol% to about 3 mol%, about 1 mol% to about 2.5 mol%, about 1 mol% to about 2 mol%, or about 1 mol% to about 1.9 mol%. If (for example, when) the manganese and aluminum contents of the nickel-manganese composite hydroxide meet any one of the above ranges, a suitably high capacity can be achieved, while the structural stability of the positive electrode active material can be increased, and the production price can be reduced to increase economic benefits.
[0086] According to one or more embodiments, a method for preparing a positive electrode active material (wherein an aluminum raw material is used to prepare a precursor of a core particle, rather than additionally doping the core particle with aluminum) can use a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly (or substantially uniformly) dispersed within the structure as a precursor of the core particle. If (for example, when) such a precursor is used, the layered structure of the positive electrode active material can be stably or appropriately maintained in the absence of cobalt despite repeated charging and discharging, and aluminum byproducts and / or aluminum aggregates may not be formed (or may not be formed in an undesirable amount), which can improve the capacity, efficiency characteristics, and cycle life characteristics of the positive electrode active material.
[0087] In the layered nickel-manganese composite hydroxide, the cobalt content (e.g., amount) may be less than or equal to about 0.01 mol%, less than or equal to about 0.005 mol%, or less than or equal to about 0.001 mol%, based on 100 mol% of the total metal. The nickel-manganese composite hydroxide may be appropriately economical because it avoids an increase in unit cost (e.g., an undesirable increase) caused by cobalt, maximizes or increases capacity, and improves structural stability.
[0088] The layered nickel-manganese-based composite hydroxide can be represented by Chemical Formula 2.
[0089] Chemical formula 2
[0090] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2.
[0091] In Formula 2, 0.6≤x2≤0.8, 0.1≤y2≤0.4, 0≤z2≤0.03, 0≤w2≤0.3, and 0.9≤x2+y2+z2+w2≤1.1, and M 2 It may be one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr.
[0092] In Chemical Formula 2, for example, 0.6≤x2≤0.8, 0.1≤y2≤0.39, 0.01≤z2≤0.03, and 0≤w2≤0.29.
[0093] The layered nickel-manganese composite hydroxide is in the form of particles, and the average particle size (D 50 ) may be about 10 μm to about 18 μm, about 11 μm to about 16 μm, or about 12 μm to about 15 μm.
[0094] The layered nickel-manganese composite hydroxide and the lithium raw material can be mixed in a molar ratio of about 1:0.9 to about 1:1.8, for example, about 1:0.9 to about 1:1.5 or about 1:0.9 to about 1:1.2. The heat treatment can be carried out under an oxygen atmosphere, for example, at about 750°C to about 950°C, about 780°C to about 900°C, or about 810°C to about 890°C for about 2 hours to about 20 hours or about 4 hours to about 12 hours. By heat treatment, a lithium nickel-manganese composite oxide can be obtained. The obtained lithium nickel-manganese composite oxide is substantially the same as the lithium nickel-manganese composite oxide described for the core particles in the positive electrode active material section.
[0095] Lithium nickel manganese composite oxides have significantly different residual lithium content (e.g., amount) and different surface properties from oxides having other compositions (e.g., nickel oxides in the related art, such as lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, etc.). For this reason, the coating method in the related art may not be able to successfully form a good or appropriate coating in the form of a uniform (or substantially uniform) film thereon. Some embodiments provide a method for improving high voltage characteristics by forming a coating having a uniform (or substantially uniform) and very or appropriately thin thickness on the surface of a lithium nickel manganese composite oxide, the lithium nickel manganese composite oxide having a very small (e.g., less than or equal to 0.1 mol% based on 100 mol% of all metals except lithium) cobalt content and a nickel content (e.g., amount) of about 60 mol% or more.
[0096] In one or more embodiments, after the Al raw material is added to the aqueous solvent and mixed, a layered lithium nickel manganese composite oxide is added thereto and mixed therewith to induce the formation of a first coating on the layered lithium nickel manganese composite oxide particles (core particles). Subsequently, a second coating is induced by adding a Ni raw material to the mixed solution and then mixing them. After the solvent is removed from the mixed solution and the residue is dried, a second heat treatment may be performed to obtain a positive electrode active material, wherein a first coating containing Al and a second coating containing Ni are sequentially formed on the surface of the core particles. This may be referred to as a continuous wet coating method.
[0097] The aqueous solvent may include distilled water, an alcohol solvent and / or any suitable combination thereof. The Al raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide and / or any suitable combination thereof. For example, the Al raw material may include aluminum sulfate, and in this case, it is beneficial to form a first coating having a uniform (or substantially uniform) thickness on the surface of the lithium nickel manganese composite oxide particles.
[0098] The Al raw material is a raw material for forming a coating layer, and the Al content (e.g., amount) in the Al raw material can be designed or selected to be about 0.1 mol% to about 2 mol%, such as about 0.2 mol% to about 1.9 mol%, about 0.3 mol% to about 1.8 mol%, about 0.5 mol% to about 1.5 mol%, or about 0.8 mol% to about 1.3 mol%, based on 100 mol% of the total metals other than lithium in the positive electrode active material finally obtained. By designing the Al content (e.g., amount) in the first coating layer to be within any one of the above ranges, a first coating layer having a suitably thin thickness of several nanometers to tens of nanometers and a uniform (or substantially uniform) thickness can be formed, reducing the amount of gas generated by the rechargeable lithium battery under high voltage and / or high temperature operating conditions, and achieving suitably high capacity and long cycle life characteristics.
[0099] The solution in which the Al raw material is added to the aqueous solvent may have a pH of about 1.5 to about 3.5, for example, about 2.0 to about 3.4, about 2.5 to about 3.3, about 2.7 to about 3.3, or about 2.9 to about 3.2. The lithium nickel manganese composite oxide is added dropwise and mixed into the aqueous solvent mixed with the aluminum raw material for about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 40 minutes. After stirring, the mixed solution may have a pH of about 4.5 to about 8.5, for example, about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0. If (for example, when) these conditions are met (when), a first coating having a uniform (or substantially uniform) thickness can be formed.
[0100] The Ni raw material may include, for example, nickel nitrate, nickel sulfate, nickel carbonate, nickel hydroxide, and / or any suitable combination thereof. Based on 100 mol% of all metals except lithium in the positive electrode active material, the Ni content (e.g., amount) in the Ni raw material may be designed or selected to be about 0.01 mol% to about 1 mol%, for example, about 0.01 mol% to about 0.9 mol%, about 0.01 mol% to about 0.7 mol%, 0.05 mol% to about 0.5 mol%, or about 0.1 mol% to about 0.4 mol%. By designing the Ni content (e.g., amount) in the second coating layer within any one of the above ranges, a second coating layer having a suitably thin thickness of several nanometers and a uniform (or substantially uniform) thickness may be formed, thereby improving the performance of the rechargeable lithium battery under high voltage and / or high temperature operating conditions, and providing suitably high capacity and long cycle life characteristics.
[0101] The addition and mixing of the Ni raw material can be carried out for about 5 minutes to about 80 minutes, or about 5 minutes to about 60 minutes, or about 10 minutes to about 40 minutes. After stirring, the pH of the final mixed solution can be about 4.5 to about 8.5, for example, about 5.0 to about 8.0, about 5.5 to about 7.5, or about 6.0 to about 7.0. If (for example, when) these conditions are met, a second coating layer of uniform (or substantially uniform) thickness can be formed.
[0102] Removal of the solvent and drying of the residue may be performed, for example, at about 40°C to about 240°C, about 100°C to about 220°C, or about 150°C to about 200°C.
[0103] The second heat treatment is carried out in an oxygen atmosphere at a temperature range of about 700°C to about 850°C, about 750°C to about 840°C, or about 800°C to about 830°C for about 2 hours to about 20 hours or about 3 hours to about 10 hours. The second heat treatment temperature may be lower than the first heat treatment temperature, and the second heat treatment time may be the same as or shorter than the first heat treatment time. A desired or appropriate coating can be obtained by performing a second heat treatment under these conditions.
[0104] Positive electrode
[0105] In one or more embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material according to the present embodiment. In addition to the above-mentioned positive electrode active material, the positive electrode active material layer may further include other types and kinds of positive electrode active materials. In an embodiment, the positive electrode active material layer may optionally further include a binder, a conductive material and / or any appropriate combination thereof.
[0106] According to one or more embodiments, the loading level of the positive electrode active material layer may be about 10 mg / cm 2 ~ about 40mg / cm 2 , for example about 10 mg / cm 2 ~about 30mg / cm 2 or about 10 mg / cm 2 ~about 20mg / cm 2 . The density of the positive electrode active material layer in the final pressed positive electrode may be about 3.3 g / cc to about 3.7 g / cc, for example, about 3.3 g / cc to about 3.6 g / cc or about 3.4 g / cc to about 3.58 g / cc. If (for example, when) the positive electrode active material according to one or more embodiments is applied, it is advantageous to implement the loading level and density of the positive electrode active material layer according to any one of the above ranges, and the positive electrode in which the loading level and density of the positive electrode active material layer satisfy any one of the above ranges may be suitable for implementing (for example, applying) a high-capacity, high-energy-density rechargeable lithium battery.
[0107] Binder
[0108] The binder improves the bonding properties of the positive electrode active material particles to each other and to the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, and nylon, but are not limited thereto.
[0109] Conductive Materials
[0110] A conductive material (e.g., an electronic conductor) is included to provide or improve electrode conductivity, and any suitable conductive material may be used as the conductive material unless it causes undesirable chemical changes in the battery. Examples of conductive materials may include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; and / or any suitable mixtures thereof.
[0111] The content (eg, amount) of the binder and the conductive material may be about 0.5 wt % to about 5 wt %, respectively, based on 100 wt % of the positive electrode active material layer.
[0112] The positive electrode current collector may include an Al foil, but the present disclosure is not limited thereto.
[0113] Rechargeable lithium battery
[0114] Some embodiments provide a rechargeable lithium battery including: a positive electrode according to the present embodiment, a negative electrode, and an electrolyte. As an example, the rechargeable lithium battery may include a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte.
[0115] Rechargeable lithium batteries may be classified into cylindrical batteries, prismatic batteries, pouch-type or quasi-batteries, coin-type or quasi-batteries, etc., depending on the shape. Figure 1 to Figure 4 A schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments. Figure 1 A cylindrical battery is shown, Figure 2 A prismatic cell is shown, and Figure 3 and Figure 4 Pouch type or similar battery is shown. Figure 1 to Figure 4 , the rechargeable lithium battery 100 includes: an electrode assembly 40 having a separator 30 disposed between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is accommodated. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte. Figure 1 As shown, the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. In one or more embodiments, Figure 2 In the embodiment, the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 3 and Figure 4 As shown, the rechargeable lithium battery 100 includes an electrode tab 70 including a positive electrode tab 71 and a negative electrode tab 72 serving as an electrical path for guiding current generated in the electrode assembly 40 to the outside.
[0116] The rechargeable lithium battery according to one or more embodiments may be rechargeable at a relatively high voltage, or may be suitable for being driven at a relatively high voltage. For example, the charging voltage of the rechargeable lithium battery may be greater than or equal to about 4.45V, about 4.45V to about 4.7V, about 4.45V to about 4.6V, or about 4.45V to about 4.55V. By applying the positive electrode active material according to one or more embodiments, the rechargeable lithium battery can significantly reduce the amount of gas generated even (for example, when) charging at a relatively high voltage, and can achieve appropriately high capacity and long cycle life characteristics.
[0117] Negative electrode
[0118] The negative electrode may include a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and may further include a negative electrode active material, a binder, a conductive material, and / or any appropriate combination thereof.
[0119] Negative electrode active material
[0120] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, and / or a transition metal oxide.
[0121] The material that can reversibly intercalate / deintercalate lithium ions may include, for example, crystalline carbon, amorphous carbon, and / or any suitable combination thereof as a carbonaceous negative electrode active material. Crystalline carbon may be amorphous and / or flaky, thin-flaked, spherical, and / or fibrous natural graphite and / or artificial graphite. Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization product, calcined coke, and the like.
[0122] Lithium metal alloys include alloys of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0123] The materials capable of doping / undoping lithium can be Si-based negative electrode active materials and / or Sn-based negative electrode active materials. The Si-based negative electrode active materials can include silicon, silicon-carbon composites, SiO x (0 < x ≤ 2), Si-Q alloys (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and / or any suitable combination thereof, such as Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and / or any suitable combination thereof) and / or any suitable combination thereof. The Sn-based negative electrode active materials can be Sn, SnO y (0 < y ≤ 2) (such as SnO2), Sn alloys, and / or any suitable combination thereof.
[0124] The silicon-carbon composite can be a composite of silicon and amorphous carbon. The average particle size (D 50 ) of the silicon-carbon composite particles (e.g., secondary particles) can be, for example, about 0.5 μm to about 20 μm. According to one or more embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, the silicon-carbon composite can include secondary particles (cores) in which silicon primary particles are aggregated and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon can also be present between the silicon primary particles. For example, the silicon primary particles can be coated with amorphous carbon. The secondary particles can be dispersed in the amorphous carbon matrix.
[0125] The silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can include: a core including crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core. The crystalline carbon can be artificial graphite, natural graphite, and / or any suitable combination thereof. The amorphous carbon can include soft carbon, hard carbon, mesophase pitch carbonization products, and / or calcined coke.
[0126] If (e.g., when) the silicon-carbon composite includes silicon and amorphous carbon, then based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon can be about 10 wt% to about 50 wt% and the content of amorphous carbon can be about 50 wt% to about 90 wt%. In one or more embodiments, if (e.g., when) the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, then based on 100 wt% of the silicon-carbon composite, the content of silicon can be about 10 wt% to about 50 wt%, the content of crystalline carbon can be about 10 wt% to about 70 wt%, and the content of amorphous carbon can be about 20 wt% to about 40 wt%.
[0127] In one or more embodiments, the thickness of the amorphous carbon coating can be about 5 nm to about 100 nm. The average particle diameter (D 50 ) of the silicon particles (primary particles) can be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles can exist as silicon alone (e.g., can be formed of silicon alone), can exist in the form of a silicon alloy, and / or be an oxidized form of silicon. The oxidized form of silicon can be represented by SiO x (0 < x ≤ 2). At this time, the ratio of the atomic content (e.g., amount) of Si:O indicating the degree of oxidation can be about 99:1 to about 33:67. As used herein, if (e.g., when) no other definition is provided otherwise, then the average particle diameter (D 50 ) indicates the diameter of the particles in which the cumulative volume in the particle size distribution is about 50 volume%.
[0128] The Si-based negative electrode active material and / or the Sn-based negative electrode active material can be mixed with the carbon-based negative electrode active material. If (e.g., when) the Si-based negative electrode active material and / or the Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, then the mixing ratio can be a weight ratio of about 1:99 to about 90:10.
[0129] Binder
[0130] The binder is used to properly or well bond the negative electrode active material particles to each other and is also used to bond the negative electrode active material to the negative electrode current collector. The binder can be a non-aqueous binder, an aqueous binder, a dry binder, and / or any suitable combination thereof.
[0131] The non-aqueous binder can include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, and / or any suitable combination thereof.
[0132] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol and / or any suitable combination thereof.
[0133] If (for example, when) an aqueous binder is used as a binder in the negative electrode active material layer, a cellulose compound capable of imparting viscosity may be further included. As the cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and alkali metal salts thereof may be mixed and used. The alkali metal may be Na, K and / or Li.
[0134] The dry binder may be a polymer material capable of becoming fibers (eg, capable of fiberizing or fibrillating), and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, and / or any suitable combination thereof.
[0135] Conductive Materials
[0136] A conductive material (e.g., an electronic conductor) is included to provide electrode conductivity, and any suitable conductive material may be used as the conductive material unless it causes undesirable chemical changes in the battery. Examples of conductive materials include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum silver, etc.; conductive polymers such as polyphenylene derivatives; and / or any suitable mixture thereof.
[0137] Based on 100wt% of the negative electrode active material layer, the content (e.g., amount) of the negative electrode active material may be about 95wt% to about 99.5wt%, and based on 100wt% of the negative electrode active material layer, the content of the binder may be about 0.5wt% to about 5wt%. For example, the negative electrode active material layer may include about 90wt% to about 99wt% of the negative electrode active material, about 0.5wt% to about 5wt% of the binder, and about 0wt% to about 5wt% of the conductive material.
[0138] Negative electrode current collector
[0139] The negative electrode current collector may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or an alloy thereof, and may be in the form of foil, sheet and / or foam. The thickness of the negative electrode current collector may be, for example, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 7 μm to about 10 μm.
[0140] Electrolytes
[0141] For example, an electrolyte for a rechargeable lithium battery may include a nonaqueous organic solvent and a lithium salt.
[0142] The non-aqueous organic solvent is used as a medium for transporting ions participating in the electrochemical reaction of the battery. The non-aqueous organic solvent may include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents and / or any appropriate combination thereof.
[0143] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In one or more embodiments, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles such as R-CN (wherein R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, and may include a double bond, an aromatic ring or an ether bond, etc.); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane, 1,4-dioxolane, etc.); cyclopentane sulfone, etc.
[0144] The non-aqueous organic solvent may be used alone or as a mixture of two or more types (kinds), and if used as a mixture of (for example, when) two or more types (kinds), the mixing ratio may be suitably or appropriately adjusted according to the desired or appropriate battery performance, which should be understood by a person of ordinary skill in the art.
[0145] If (for example, when) a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed and used, and the cyclic carbonate and the chain carbonate may be mixed in a volume ratio of about 1:1 to about 1:9.
[0146] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, a carbonate-based solvent and an aromatic hydrocarbon organic solvent may be mixed and used in a volume ratio of about 1:1 to about 30:1.
[0147] The electrolyte may further include vinyl ethylene carbonate, vinylene carbonate and / or ethylene carbonate-based compounds to improve the battery cycle life.
[0148] Examples of the ethylene carbonate-based compound may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0149] The lithium salt dissolved in the organic solvent supplies lithium ions in the battery, ensures or facilitates the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFBOP) and lithium bis(oxalato)borate (LiBOB).
[0150] The concentration of the lithium salt may be in the range of about 0.1 M to about 2.0 M. If (for example, when) the concentration of the lithium salt is within the above range, the electrolyte has suitable or appropriate ion conductivity and viscosity, and thus excellent or appropriate performance may be achieved, and lithium ions may be efficiently or appropriately moved.
[0151] Diaphragm
[0152] Depending on the type (or kind) of the rechargeable lithium battery, the separator may be present between the positive electrode and the negative electrode. The separator may include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, and / or a multilayer film of two or more layers thereof (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).
[0153] The separator may include a porous substrate and a coating on a surface (eg, on one or both surfaces (eg, opposite surfaces or sides)) of the porous substrate, the coating including an organic material, an inorganic material, and / or any suitable combination thereof.
[0154] The porous substrate may be a polymer film formed from any one of the following polymers or a copolymer or mixture thereof: polyolefin (such as polyethylene and / or polypropylene), polyester (such as polyethylene terephthalate and / or polybutylene terephthalate), polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber and polytetrafluoroethylene. Any one of the foregoing, or a copolymer or mixture of two or more thereof.
[0155] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0156] The organic material may include: a structural unit derived from (meth)acrylamide sulfonic acid or a salt thereof; and a (meth)acryl-based copolymer, the (meth)acryl-based copolymer including a first structural unit derived from (meth)acrylamide and a second structural unit including at least one of a structural unit derived from (meth)acrylic acid and a structural unit derived from (meth)acrylate.
[0157] The inorganic material may include inorganic particles (e.g., in the form of inorganic particles) selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and / or any suitable combination thereof, but the present disclosure is not limited thereto. The average particle size (D 50 ) may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.
[0158] An organic material and an inorganic material may be mixed in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.
[0159] The coating layer may have a thickness of about 0.5 μm to about 20 μm, for example, about 1 μm to about 10 μm or about 1 μm to about 5 μm.
[0160] Hereinafter, embodiments and comparative examples of the present disclosure are described in more detail. However, the following embodiments are merely examples of the present disclosure, and the present disclosure is not limited to the following embodiments.
[0161] Example 1
[0162] 1. Preparation of positive electrode active material
[0163] Ni 0.75 Mn 0.23 Al 0.02 (OH)2 and LiOH were mixed in a molar ratio of 1:1 and then subjected to a first heat treatment at 850°C for 8 hours in an oxygen atmosphere to prepare a secondary particle having LiNi 0.75 Mn 0.23 Al 0.02 O2 composition and an average particle size of about 14 μm (D 50 ) of lithium nickel manganese composite oxide.
[0164] After aluminum sulfate is mixed with distilled water solvent, the prepared lithium nickel manganese composite oxide is added thereto, and then mixed for 20 minutes to 60 minutes. In this article, based on 100mol% of the total metal other than lithium in the final positive electrode active material, the aluminum content (e.g., amount) in aluminum sulfate is designed (e.g., set) to 1.0mol%. Next, nickel sulfate is added and mixed for about 10 minutes to 40 minutes. In this article, based on 100mol% of the total metal other than lithium in the final positive electrode active material, the nickel content (e.g., amount) in nickel sulfate is designed (or set) to 0.2mol%. After removing the solvent from the mixed solution and drying the residue at 190°C, a second heat treatment is performed at 825°C in an oxygen atmosphere for 8 hours to prepare the final positive electrode active material.
[0165] 2. Preparation of rechargeable lithium battery cells
[0166] Based on the total weight of the positive electrode active material layer slurry, 98.5wt% of the positive electrode active material, 1.0wt% of the polyvinylidene fluoride binder and 0.5wt% of the carbon nanotube conductive material were mixed to prepare the positive electrode active material layer slurry, and the slurry was coated on an aluminum foil positive electrode current collector, and then dried and pressed to prepare a positive electrode. In this article, the positive electrode active material layer has 10mg / cm 2 The loading level was , and the positive electrode active material layer in the final pressed positive electrode had a density of about 3.4 g / cc.
[0167] Based on the total weight of the negative electrode active material layer slurry, 97.5wt% of graphite negative electrode active material, 1.5wt% of carboxymethyl cellulose and 1wt% of styrene butadiene rubber were mixed in an aqueous solvent to prepare a negative electrode active material layer slurry. The negative electrode active material layer slurry was coated on a copper foil negative electrode current collector, and then dried and pressed to prepare a negative electrode.
[0168] A rechargeable lithium battery cell was prepared using a polytetrafluoroethylene separator and an electrolyte prepared by dissolving 1M LiPF6 in a mixed solvent of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7 using one or more appropriate methods in the art.
[0169] Comparative Example 1
[0170] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the LiNi 0.75 Mn 0.23 Al 0.02 O2 itself is a lithium nickel manganese composite oxide used as the positive electrode active material.
[0171] Comparative Example 2
[0172] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by dry coating only Al without coating Ni.
[0173] Al dry coating is performed in the following manner. 0.75 Mn 0.23 Al 0.02 A lithium nickel manganese based composite oxide composed of O2 was mixed with alumina powder, and then the mixture was heat treated at 825°C for 8 hours in an oxygen atmosphere to dry-coat Al to prepare a positive electrode active material.
[0174] Comparative Example 3
[0175] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by wet coating only Al without coating Ni.
[0176] For example, a positive electrode active material is prepared by mixing aluminum sulfate with a distilled water solvent, adding a lithium nickel manganese composite oxide thereto, mixing them for 20 to 60 minutes, removing the solvent therefrom, drying the residue at 190° C., and performing a second heat treatment at 825° C. for 8 hours in an oxygen atmosphere.
[0177] Comparative Example 4
[0178] A positive electrode active material and a rechargeable lithium battery cell were prepared in substantially the same manner as in Example 1, except that the positive electrode active material was prepared by wet coating only Ni without coating Al.
[0179] For example, a positive electrode active material is prepared by adding a lithium nickel manganese composite oxide to a distilled water solvent, adding nickel sulfate thereto to mix them (e.g., the resulting mixture) for about 10 to 40 minutes, removing the solvent therefrom, drying the residue at 190° C., and performing a second heat treatment at 825° C. for 8 hours in an oxygen atmosphere.
[0180] Evaluation Example 1: Analysis of Positive Electrode Active Material
[0181] The positive electrode active material particles prepared in Example 1 were cut using a focused ion beam (FIB) to obtain a cross section, which was examined by EDS and HR-STEM analysis. Figure 5 is a HR-STEM image of a cross section of the positive electrode active material of Example 1, which is an image obtained by magnifying a primary particle located at the outermost surface in a cross section of a secondary particle. Figure 6 As highlighted by EDS analysis Figure 5 The image of the nickel element in Figure 7 As highlighted by EDS analysis Figure 5 Image of the aluminum element in . Figure 5 to Figure 7 A first coating layer containing Al is formed on the surface of the secondary particle with a uniform (or substantially uniform) thickness, and a second coating layer containing Ni is formed on the first coating layer with a uniform (or substantially uniform) thickness, the first coating layer and the second coating layer as a whole forming an overall uniform (or substantially uniform) double coating layer, providing a positive electrode active material having a dual core-shell structure.
[0182] Evaluation Example 2: Charge and discharge characteristics and high temperature cycle life characteristics
[0183] At 25°C, the rechargeable lithium battery cells according to Example 1 and Comparative Examples 1 to 4 were charged to 4.45V at a constant current of 0.2C and charged to 0.05C at a constant voltage, and then discharged to 3.0V at 0.2C as initial charge and discharge, wherein the initial discharge capacity (i.e., 4.45V initial discharge capacity) was measured. And the 4.45V initial discharge capacity of the rechargeable lithium battery cells is shown in Table 1.
[0184] Subsequently, at 45° C., the rechargeable lithium battery cell was charged at 1.0C and discharged at 1.0C in a voltage range of 3.0V to 4.45V, repeated 25 times, and then, the ratio of the discharge capacity after the 25th cycle to the initial discharge capacity was calculated, which is shown in Table 1 as the high temperature cycle life.
[0185] (Table 1)
[0186]
[0187] Referring to Table 1, the rechargeable lithium battery cell of Example 1 exhibits superior or improved initial discharge capacity and high temperature cycle-life characteristics compared to the rechargeable lithium battery cells of Comparative Examples 1 to 4.
[0188] While the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it should be understood that the present disclosure is not limited to the disclosed embodiments. Instead, the present disclosure is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the claims and their equivalents.
Claims
1. A positive electrode active material comprising: The core particle includes a layered lithium nickel manganese composite oxide, a first coating layer, on the surface of the core particle and comprising Al, and A second coating layer is on the first coating layer and includes Ni.
2. The positive electrode active material according to claim 1, wherein In the layered lithium nickel manganese composite oxide of the core particle, The amount of nickel is 60 mol % to 80 mol % and the amount of manganese is greater than or equal to 10 mol % based on 100 mol % of all metals except lithium in the layered lithium nickel manganese-based composite oxide.
3. The positive electrode active material according to claim 1, wherein The layered lithium nickel manganese based composite oxide of the core particle further includes aluminum, and the amount of aluminum is greater than 0 mol % and less than or equal to 3 mol % based on 100 mol % of all metals except lithium in the layered lithium nickel manganese based composite oxide.
4. The positive electrode active material according to claim 1, wherein In the layered lithium nickel manganese composite oxide of the core particle, The amount of cobalt is at most 0.01 mol % based on 100 mol % of all metals except lithium in the layered lithium nickel manganese-based composite oxide.
5. The positive electrode active material according to claim 1, wherein The layered lithium nickel manganese-based composite oxide of the core particle is represented by Chemical Formula 1: Chemical formula 1 Li a1 Ni x1 Mr y1 Al z1 M 1 w1 O 2-b1 X b1 , In Chemical Formula 1, 0.9≤a1≤1.8, 0.6≤x1≤0.8, 0.1≤y1≤0.4, 0≤z1≤0.03, 0≤w1≤0.3, 0.9≤x1+y1+z1+w1≤1.1, and 0≤b1≤0.1, M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more elements selected from F, P and S.
6. The positive electrode active material according to claim 1, wherein The first coating layer and the second coating layer are each in the form of a continuous film.
7. The positive electrode active material according to claim 1, wherein The thickness of the first coating is 5nm to 40nm, and The thickness of the second coating layer is less than or equal to 10 nm.
8. The positive electrode active material according to claim 1, wherein A ratio of a thickness of the second coating layer to a thickness of the first coating layer is less than 0.
5.
9. The positive electrode active material according to claim 1, wherein The amount of Al in the first coating layer is 0.1 mol% to 2 mol% based on 100 mol% of all metals except lithium in the positive electrode active material, and The amount of Ni in the second coating layer is 0.01 mol % to 1 mol % based on 100 mol % of all metals except lithium in the positive electrode active material.
10. The positive electrode active material according to claim 1, wherein The amount of Al in the first coating layer is 0.5 mol% to 1.5 mol% based on 100 mol% of all metals except lithium in the positive electrode active material, and The amount of Ni in the second coating layer is 0.05 mol% to 0.5 mol% based on 100 mol% of all metals except lithium in the positive electrode active material.
11. The positive electrode active material according to claim 1, wherein The ratio of the amount of Ni in the second coating layer to the amount of Al in the first coating layer is less than 0.
5.
12. The positive electrode active material according to claim 1, wherein The first coating comprises aluminum oxide, lithium aluminum oxide, or a combination thereof, and The second coating layer includes nickel oxide, lithium nickel oxide, aluminum nickel oxide, lithium aluminum nickel oxide, or a combination thereof.
13. The positive electrode active material according to claim 1, wherein The first coating layer and the second coating layer each have a layered structure.
14. The positive electrode active material according to claim 1, wherein The core particle is a secondary particle made by aggregating a plurality of primary particles, and The positive electrode active material further includes a grain boundary coating portion including Al on the surface of the primary particle inside the secondary particle.
15. The positive electrode active material according to claim 14, wherein The amount of Al in the grain boundary coating portion is smaller than the amount of Al in the first coating layer based on 100 mol % of total metals excluding lithium in the positive electrode active material.
16. The positive electrode active material according to claim 1, wherein The positive electrode active material is in the form of secondary particles and the average particle size D of the secondary particles is 50 It is 10μm~20μm.
17. A method for preparing a positive electrode active material, the method comprising: The layered nickel-manganese composite hydroxide and the lithium raw material are mixed and subjected to a first heat treatment to obtain a layered lithium-nickel-manganese composite oxide, adding an Al raw material to an aqueous solvent, adding the layered lithium nickel manganese-based composite oxide thereto and mixing, then adding a Ni raw material and mixing, and The mixture is dried and subjected to a second heat treatment.
18. The method of claim 17, wherein: In the layered nickel-manganese composite hydroxide, The amount of nickel is 60 mol% to 80 mol%, The amount of manganese is greater than or equal to 10 mol%. The amount of aluminum is at most 3 mol%, and The amount of cobalt is at most 0.01 mol%. Each of the amount of nickel, the amount of manganese, the amount of aluminum, and the amount of cobalt is based on 100 mol % of all metals in the layered nickel-manganese-based composite hydroxide.
19. The method of claim 17, wherein The amount of Al in the Al raw material is 0.1 mol% to 2 mol% based on 100 mol% of all metals except lithium in the positive electrode active material, and The amount of Ni in the Ni raw material is 0.01 mol % to 1 mol % based on 100 mol % of all metals except lithium in the positive electrode active material.
20. The method of claim 17, wherein The Al raw material includes aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide or a combination thereof, and The Ni raw material includes nickel nitrate, nickel sulfate, nickel carbonate, nickel hydroxide or a combination thereof.
21. The method of claim 17, wherein The solution in which the Al raw material is added to the aqueous solvent has a pH of 1.5 to 3.
5.
22. The method of claim 17, wherein The first heat treatment is performed at 750°C to 950°C, and The second heat treatment is performed at 700°C to 850°C.
23. A positive electrode comprising: a positive electrode current collector, and A positive electrode active material layer, on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to claim 1 or a positive electrode active material prepared by the method according to any one of claims 17 to 22.
24. The positive electrode of claim 23, wherein The positive electrode active material layer has a 10 mg / cm 2 ~40mg / cm 2 load level.
25. The positive electrode of claim 23, wherein The positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.
26. A rechargeable lithium battery comprising: The positive electrode according to claim 23, negative electrode, and Electrolytes.
27. The rechargeable lithium battery of claim 26, wherein: The charging voltage of the rechargeable lithium battery is greater than or equal to 4.45V.